2007
DOI: 10.1007/s00267-006-0019-y
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Spatial Clustering and Implications for Wildlife Management: A Burrowing Owl Example

Abstract: Analysis tools that combine large spatial and temporal scales are necessary for efficient management of wildlife species, such as the burrowing owl (Athene cunicularia). We assessed the ability of Ripley's K-function analysis integrated into a geographic information system (GIS) to determine changes in burrowing owl nest clustering over two years at NASA Ames Research Center. Specifically, we used these tools to detect changes in spatial and temporal nest clustering before, during, and after conducting managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…The use of spatial statistics for this purpose consists of three parts: average nearest neighbor index (ANNI), p-value, and z-score calculations. The average nearest neighbor index has been used to determine clustering of epidemics, diseases (Delgado et al, 2008;Kan et al, 2008;Lai et al, 2004), natural phenomenon (Bishop, 2010(Bishop, , 2007Guiqin et al, 2009), and population demographic densities (Austin et al, 2005;Çelik et al, 2010;Fisher et al, 2007;Yildiz et al, 2004). It compares the observed mean distance D O between each feature and its nearest neighbor with the expected mean distance D E for a feature in a random pattern (normal distribution) as shown in equation (1) (Alves et al, 2009;Smith et al, 2007).…”
Section: Pv Diffusion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of spatial statistics for this purpose consists of three parts: average nearest neighbor index (ANNI), p-value, and z-score calculations. The average nearest neighbor index has been used to determine clustering of epidemics, diseases (Delgado et al, 2008;Kan et al, 2008;Lai et al, 2004), natural phenomenon (Bishop, 2010(Bishop, , 2007Guiqin et al, 2009), and population demographic densities (Austin et al, 2005;Çelik et al, 2010;Fisher et al, 2007;Yildiz et al, 2004). It compares the observed mean distance D O between each feature and its nearest neighbor with the expected mean distance D E for a feature in a random pattern (normal distribution) as shown in equation (1) (Alves et al, 2009;Smith et al, 2007).…”
Section: Pv Diffusion Modelmentioning
confidence: 99%
“…Previous research has proposed various strategies and infrastructure configurations for EoL PV recovery that mimic other products, for example, extended producer responsibility for nickelecadmium (NiCd) batteries, centralized second-party collection for CRT monitors, and decentralized processing such as what exists for municipal solid waste (Austin et al, 2005;Eberspacher and Fthenakis, 1997;Fisher et al, 2007;Fthenakis, 2000). Although recycling has been proposed to reduce the lifecycle impact of photovoltaics, (Goe and Gaustad, 2014a;Müller et al, 2006;Smith et al, 2007) there is uncertainty about the environmental impacts of technologies employed and transportation required for recovery.…”
Section: Introductionmentioning
confidence: 98%
“…Burrows or mounds are often used as spatial reference for the distribution of specimens or colonies of the target species. For example, Fisher et al (2007) investigated the spatial clustering of burrows of a ground-living owl, Schooley and Wiens (2001) analysed kangaroo rat mounds in New Mexico and Crist and Wiens (1996) deduced, from the distribution of ant colonies, implications for ecosystem processes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the presence of active colonies helps to explain much of the variation in burrowing owl abundance, we found that the spatial autocorrelation of these colonies very weakly explained some of this variation. Other studies have investigated the spatial arrangement of owl nests within colonies (Desmond et al , Fisher et al ), but not how the spatial arrangement of colonies affects owl abundance. The estimates for our range parameter suggest that the spatial process in our data had influence over a very short distance (about 3% of colonies were separated by distances ≤10 km).…”
Section: Discussionmentioning
confidence: 99%
“…In actuality, though, this solution would probably be implemented over time, which could mean that the static solution would no longer be optimal. Additionally, land in western Nebraska is largely privately owned and managers may need to overcome substantial political hurdles when implementing conservation strategies focused on prairie dog colonies (Fisher et al ). This raises the possibility that a strategy would have to be implemented in an opportunistic way and trade‐offs would have to be made in terms of whether to take implementation opportunities or wait for new opportunities that arise stochastically.…”
Section: Discussionmentioning
confidence: 99%